On a Planar Dynamical System Arising in the Network Control Theory - Atslega, Svetlana; Finaskins, Dmitrijs; Sadyrbaev, Felix (Mathematical Modelling and Analysis, 2016)
We study the structure of attractors in the two-dimensional dynamical system that appears in the network control theory. We provide description of the attracting set and follow changes this set suffers under the changes of positive parameters µ and Θ.